Leiomyosarcoma of the vulva: a case report - Teramae, Masatomo; Fukuda, Takeshi; Imai, Kenji; Yamauchi, Makoto; Hashiguchi, Yasunori; Ichimura, Tomoyuki; Yasui, Tomoyo; Sumi, Toshiyuki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Sarcomas represent only 1% to 3% of vulvar malignancies. Leiomyosarcoma is a rare malignant tumor of the vulva; it can be mistaken for a benign tumor, which can lead to misdiagnosis and incorrect or delayed treatment. We report the case of a 51-year-old woman with leiomyosarcoma of the vulva. The patient presented to her primary gynecologist with a vulvar mass that she had first noticed 20 years prior. The tumor was suspected to be aggressive angiomyxoma, and biopsy of the mass and treatment with gonadotrophin-releasing hormone agonist (GnRHa) therapy were recommended. The patient declined treatment and opted instead for observation; however, the tumor grew rapidly in the following year and the patient was referred to our hospital. She underwent tumor resection, and pathology revealed leiomyosarcoma. The patient declined adjuvant chemo- and radiotherapy but has had no recurrence for 32 months.